Peranan Penyuluhan Kesehatan Reproduksi Remaja dalam Mencegah Kehamilan di Luar Nikah - Oktaria, Wita; Suryati, Suryati; Puspita Dewi, Emi (Berkala Ilmiah Pendidikan, 2024)
This research is entitled "The Role of Adolescent Reproductive Health Counseling in Preventing Pregnancy Out of Wedlock at the Indonesian Family Planning Association (PKBI) Palembang". Cases of pregnancy out of wedlock, especially in Indonesia, are increasing as evidenced by the many requests for marriage and abortion dispensations carried out in the year, The increasing prevalence of this makes the values ​​and norms that society upholds increasingly fade. This research aims to, namely, find out the counseling strategies implemented in preventing out-of-wedlock pregnancies and find out the role of adolescent reproductive health education in preventing out-of-wedlock pregnancies using research type research (hands-on research) with descriptive qualitative methods. The data collection techniques used were observation, interviews and documentation. The subjects of this research were 1 executive director of the Indonesian Family Planning Association PKBI Palembang, 2 counselors and 2 teenagers. which is analyzed using data reduction, data display and conclusions. The results of the research show that teenagers' knowledge regarding reproductive health is sufficient to understand promiscuity and pregnancy outside of marriage because this often happens in the environment around them. However, some teenagers do not yet know the dangers to reproductive health if they engage in promiscuity and there is a lack of desire among teenagers to seek information. There are 2 adolescent reproductive health education strategies that are implemented to prevent pregnancy out of wedlock, namely online and offline. Based on the results of research regarding counseling carried out by PKBI, it has a role for teenagers in preventing pregnancy outside of marriage, such as teenagers being able to understand reproductive health, teenagers being able to develop positive effects on reproductive health, knowing the impact on their reproductive health so that extramarital pregnancies do not occur again.